A Microbiome-Driven Approach to Combating Depression During the COVID-19 Pandemic - Ghannoum, Mahmoud A.; Ford, MaryKate; Bonomo, Robert A.; Gamal, Ahmed; McCormick, Thomas S. (Frontiers in Nutrition, 2021)
The significant stressors brought about and exacerbated by COVID-19 are associated with startling surges in mental health illnesses, specifically those related to depressive disorders. As a result of society's imperfect understanding and inability to adequately treat depression and depressive symptoms, we have examined the current literature surrounding the microbiome and gut-brain axis to develop a potential new approach to address such disorders. While we understand that the impact of the human gut microbiome on emotional health is a newly emerging field and more research needs to be conducted, the current evidence is extremely promising and suggests at least part of the answer to managing depression may lie within the microbiome. As a result of these findings, we advance the notion that a microbiome-based holistic approach, which involves rebalancing the microbiome through diet, probiotics, and lifestyle changes, may address depression. This paper's primary purpose is to shed light on the link between the gut microbiome and depression, including the gut-brain axis and propose a holistic approach to rebalance the microbiome, with the ultimate goal of assisting individuals to manage their battle with depression through diet, probiotics, and lifestyle changes, in addition to offering a semblance of hope during these challenging times.